2005
DOI: 10.1099/mic.0.28243-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an upstream regulatory sequence that mediates the transcription of mox genes in Methylobacterium extorquens AM1

Abstract: A multiple A-tract sequence has been identified in the promoter regions for the mxaF, pqqA, mxaW, mxbD and mxcQ genes involved in methanol oxidation in Methylobacterium extorquens AM1, a facultative methylotroph. Site-directed mutagenesis was exploited to delete or change this conserved sequence. Promoter-xylE transcriptional fusions were used to assess promoter activity in these mutants. A fiftyfold drop in the XylE activity was observed for the mxaF and pqqA promoters without this sequence, and a five-to six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…The results described above suggested that Ecm was functioning as a control point during the transition from growth on succinate to growth on ethylamine, restricting the consumption of ethylmalonyl-CoA and the production of downstream intermediates during the lag period of the transition. To test this model, we overrode the control point by overexpressing ecm from a strong promoter (the mxaF promoter) that is highly expressed during growth on both succinate and ethylamine (16,37). Ecm activity increased 4-fold (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The results described above suggested that Ecm was functioning as a control point during the transition from growth on succinate to growth on ethylamine, restricting the consumption of ethylmalonyl-CoA and the production of downstream intermediates during the lag period of the transition. To test this model, we overrode the control point by overexpressing ecm from a strong promoter (the mxaF promoter) that is highly expressed during growth on both succinate and ethylamine (16,37). Ecm activity increased 4-fold (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The lacZ gene of pCM132 was deleted and replaced by a 33-bp multiple cloning site to generate pHC41. The promoter-probe plasmid, pHC42, was generated by cloning a 734-bp PCR fragment containing the ribosome binding site (RBS) of the fae gene (encoding formaldehyde-activating enzyme) of Methylobacterium and the reporter GFPuv gene from pKF133 into pHC41 [73],[74]. A 51-bp synthetic fragment containg the constitutive promoter P tac was inserted upstream of this reporter to make pHC62.…”
Section: Methodsmentioning
confidence: 99%
“…Also, MxcQ and MxcE, another putative two component regulatory system, are required for the expression of mxaF, the gene for the large subunit of methanol dehydrogenase (MDH) (37). Further, a methanol-inducible promoter with a multi-A tract sequence upstream of mxaF is essential for the expression of mxaF (22,39). In Paracoccus denitrificans, genes involved in methanol oxidation are located in the mxa gene cluster (38).…”
mentioning
confidence: 99%